2021
DOI: 10.1016/j.celrep.2021.110094
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 affects synaptic plasticity and cognition in an experimental model of multiple sclerosis

Abstract: Highlights d Hippocampal neurons express IL-17RA both under control conditions and during EAE d IL-17A dose-dependently blocks LTP via the activation of IL-17RA and p38 MAPK d Hippocampal IL-17A overexpression and synaptic dysfunction both occur during EAE d The lack of IL-17A ameliorates EAE-related cognitive deficits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…During EAE, meningeal Th17 cells drive neuroinflammation by producing proinflammatory IL17A, further recruitment of leukocytes into the meninges, and induction of follicular meningeal B cell activation [51,52] . A similar phenomenon is recorded in ischemic brain injury models where T cell infiltration and IL17 production drives cerebral infarction [53,54] . IL17A can also be directly recognized by IL17RA expressing hippocampal neurons, which induce dysfunctional hippocampal long-term potentiation and significant cognitive impairments [55] .…”
Section: Meningeal T Cellssupporting
confidence: 63%
“…During EAE, meningeal Th17 cells drive neuroinflammation by producing proinflammatory IL17A, further recruitment of leukocytes into the meninges, and induction of follicular meningeal B cell activation [51,52] . A similar phenomenon is recorded in ischemic brain injury models where T cell infiltration and IL17 production drives cerebral infarction [53,54] . IL17A can also be directly recognized by IL17RA expressing hippocampal neurons, which induce dysfunctional hippocampal long-term potentiation and significant cognitive impairments [55] .…”
Section: Meningeal T Cellssupporting
confidence: 63%
“…It was also shown that under the hypoxia condition exposure to LPS could depress the post-synaptic efficacy of glutamate receptors by the superoxide and nitric oxide production (Zhang et al, 2014 ). The number of studies on such immune-triggered modulations of synaptic transmission in the CNS is increasing these days (Pascual et al, 2012 ; Parkhurst et al, 2013 ; Zhan et al, 2014 ; Zhang et al, 2014 ; Yamamoto et al, 2019 ; Di Filippo et al, 2021 ). Therefore, brain immunity is the triggering factor of synaptic plasticity via immune receptors, such as pattern-recognition receptors and cytokine receptors, expressed in the neurons.…”
Section: Microglia Heterogeneity and Roles For Modulating Activity Of...mentioning
confidence: 99%
“…Monoclonal anti-IL-17B histochemistry displays its expression in neurons and glial cells in the cerebellum, hippocampus, and cerebral cortex (Moore et al, 2002 ). IL-17A is also studied in the mouse models of neuropathic pain and multiple sclerosis (Luo et al, 2019 ; Di Filippo et al, 2021 ). Luo et al ( 2019 ) demonstrated that IL-17A is mainly released from spinal cord astrocytes, and its receptor IL-17R exists in somatostatin-expressing interneurons.…”
Section: Roles Of Inflammatory Cytokines and Lipid Mediators In Synap...mentioning
confidence: 99%
See 2 more Smart Citations